2014
DOI: 10.1063/1.4862443
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of low Reynolds number non-Boussinesq fountains from non-circular sources

Abstract: The behaviour of low Reynolds number, non-Boussinesq fountains from four different nozzle geometries (one circular and three rectangular nozzles) are studied. High speed laser schlieren imaging is used to study the fountain behaviour (frequency and penetration height). Bi-orthogonal decomposition and dynamic mode decomposition (DMD) are used to understand the unsteady characteristics of fountains. The flow regimes of fountains are classified as steady, flapping, and flapping-bobbing type. The DMD technique suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…This is a common feature of elongated fountains (i.e. H m b i ), for which a radius-independent 'bobbing' behaviour is observed (see Vinoth & Panigrahi 2014).…”
Section: Fountain Fluctuationsmentioning
confidence: 94%
“…This is a common feature of elongated fountains (i.e. H m b i ), for which a radius-independent 'bobbing' behaviour is observed (see Vinoth & Panigrahi 2014).…”
Section: Fountain Fluctuationsmentioning
confidence: 94%
“…Although studies on fountains commenced in the 1950s (see, e.g., [1]), they are still being extensively investigated (see, e.g., [2][3][4][5][6][7][8][9][10][11][12]). However, the studies have focused on round fountains, which may be either 'very weak' when F r 1, or 'weak' when 1 F r 3, or 'forced' when F r 3, as classified by Kaye and Hunt [13] and Burridge and Hunt [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not surprising that their rise heights scale differently. Likewise, experiments on rectangular sources by Vinoth & Panigrahi (2014) have shown that large source ratios are required at the source to attain the two-dimensional scaling. In our experiments, it is questionable whether the upflowing core, which remains slender (e.g.…”
Section: Rise Heights and Lateral Excursionsmentioning
confidence: 99%
“…There are many techniques available to extract temporal information from a series of snapshots or signals. Decomposition methods, for instance, have successfully separated different oscillating modes in low-Re 0 fountains in Vinoth & Panigrahi (2014). Burridge & Hunt (2013), in their study of fluctuations at the (unconfined) fountain top, performed Fourier transforms of the rise height signal z f (t) to identify dominant frequencies.…”
Section: Frequenciesmentioning
confidence: 99%